Assessment of carbon neutrality of building materials using emergy parameter. (11th April 2023) - Thomas, Tilba; Praveen, A.; Ajitha, T.
Development of appropriate tools and techniques are essential for the reliable assessment of carbon footprint of building systems. Comprehensive assessment of both energy and carbon emissions attributed to different building materials and correlating it with the emergy values is established as an effective tool for assessing the sustainability. This research further emphasises the utility of unit emergy value of carbon dioxide emissions for various building materials to assess their carbon neutrality potential. Thus, significance of emergy parameters in the judicious selection of building materials to curb carbon accumulation is established here.